Date | None Specimen | Marks available | 11 | Reference code | SPNone.2.hl.TZ0.5 |
Level | HL only | Paper | 2 | Time zone | TZ0 |
Command term | Determine, Hence, Show that, and Solve | Question number | 5 | Adapted from | N/A |
Question
Consider the differential equation\[\frac{{{\text{d}}y}}{{{\text{d}}x}} + y\sec x = x(\sec x - \tan x),{\text{ where }}y = 3{\text{ when }}x = 0.\]
Use Euler’s method with a step length of \(0.1\) to find an approximate value for \(y\) when \(x = 0.3\) .
(i) By differentiating the above differential equation, obtain an expression involving \(\frac{{{{\rm{d}}^{\rm{2}}}y}}{{{\rm{d}}{x^2}}}\) .
(ii) Hence determine the Maclaurin series for \(y\) up to the term in \({{x^2}}\) .
(iii) Use the result in part (ii) to obtain an approximate value for \(y\) when \(x = 0.3\) .
(i) Show that \(\sec x + \tan x\) is an integrating factor for solving this differential equation.
(ii) Solve the differential equation, giving your answer in the form \(y = f(x)\) .
(iii) Hence determine which of the two approximate values for y when \(x = 0.3\) , obtained in parts (a) and (b), is closer to the true value.
Markscheme
Note: The A1 marks above are for correct entries in the \(y\) column.
\(y(0.3) \approx 2.21\) A1
[5 marks]
(i) use of product rule on either side M1
\(\frac{{{{\rm{d}}^{\rm{2}}}y}}{{{\rm{d}}{x^2}}} + \sec x\frac{{{\rm{d}}y}}{{{\rm{d}}x}} + y\sec x\tan x = \sec x - \tan x + x(\sec x\tan x - {\sec ^2}x)\) A1A1
(ii) \(y(0) = 3\)
\(y'(0) = - 3\), \(y''(0) = 4\) A1A1
the quadratic approximation is
\(y = \left( {y(0) + xy'(0) + |\frac{{{x^2}y''(0)}}{2} = } \right)3 - 3x + 2{x^2}\) (M1)A1
(iii) using this approximation, \(y(0.3) \approx 2.28\) A1
[8 marks]
(i) EITHER
\(\frac{{\rm{d}}}{{{\rm{d}}x}}(\sec x + \tan x) = \sec x\tan x + {\sec ^2}x\) A1
\(\sec x(\sec x + \tan x) = {\sec ^2}x + \sec x\tan x\) A1
as these two expressions are the same, this is an integrating factor R1AG
OR
\((\sec x + \tan x)\left( {\frac{{{\rm{d}}y}}{{{\rm{d}}x}} + y\sec x} \right) = (\sec x + \tan x)x(\sec x - \tan x)\) M1
Note: RHS does not need to be shown.
\({\rm{LHS}} = \frac{{{\rm{d}}y}}{{{\rm{d}}x}}(\sec x + \tan x) + y(\sec x|\tan x + {\sec ^2}x)\) A1
\( = \frac{{\rm{d}}}{{{\rm{d}}x}}y(\sec x + \tan x)\) A1
making LHS an exact derivative
OR
integrating factor \( = {{\rm{e}}^{\int {\sec x{\rm{d}}x} }}\) M1
since \(\frac{{\rm{d}}}{{{\rm{d}}x}}\ln (\sec x + \tan x) = \frac{{\sec x\tan x + {{\sec }^2}x}}{{\sec x + \tan x}} = \sec x\) M1A1
integrating factor \( = {{\rm{e}}^{\ln (\sec x + \tan x)}} = \sec x + \tan x\) AG
(ii) \(\frac{{\rm{d}}}{{{\rm{d}}x}}(y\left[ {\sec x + \tan x} \right]) = x({\sec ^2}x - {\tan ^2}x) = x\) M1A1
\(y(\sec x + \tan x) = \frac{{{x^2}}}{2} + c\) A1
\(x = 0,y = 3 \Rightarrow c = 3\) M1A1
\(y = \frac{{{x^2} + 6}}{{2(\sec x + \tan x)}}\) A1
(iii) when \(x = 0.3,y = 2.245 \ldots \) A1
the closer approximation is obtained by using the series in part (b) R1
[11 marks]